Strengthening Indonesian Equivalents on the Instagram Account @narabahasa: A Critical Discourse Analysis by Norman Fairclough - Aisyah, Rohani Nur; Hardinanto, Eko (Jurnal Bahasa Indonesia Prima (BIP), 2026)
Strengthening Indonesian language equivalents in the digital space is a strategic effort to liberate the Indonesian language amid the dominance of foreign terms. The Instagram account @narabahasa serves as an informal institution that provides accurate and educational linguistic information to bridge the gap between formal language and language practices among the public. This study aims to describe the forms of Indonesian equivalents presented in the texts and visuals posted on the Instagram account @narabahasa, analyze discourse practices in efforts to strengthen Indonesian equivalents, and reveal the socio-cultural implications of the discourse on strengthening Indonesian equivalents. This study uses a qualitative approach with Norman Fairclough's critical discourse analysis method, including text analysis, discourse practices, and socio-cultural practices. The research data consists of posts and captions from the Instagram account @narabahasa that contain contextual discourse on Indonesian language equivalents. The results of the study show that the @narabahasa account not only functions as a medium for language education but also as a digital medium that plays a significant role in shaping the language awareness of the community. This study reveals that the process of term equivalence in the digital space involves power relations, meaning negotiation, and the construction of linguistic identity within the digital community.